Residues on both faces of the first immunoglobulin fold contribute to homophilic binding sites of PECAM-1/CD31. - Newton, J; Buckley, C; Jones, E; Simmons, D (1997)
CD31 (PECAM-1) is a member of the immunoglobulin superfamily whose extracellular domain is comprised of six immunoglobulin-like domains. It is widely expressed on endothelium, platelets, around 50% of lymphocytes, and cells of myeloid lineage. CD31 has been shown to be involved in interendothelial adhesion and leukocyte-endothelial interactions, particularly during transmigration. CD31-mediated adhesion is complex, because CD31 is capable of mediating both homophilic and multiple heterophilic adhesive interactions. Here we show that the NH2-terminal (membrane-distal) immunoglobulin domain of CD31 is necessary but not sufficient to support stable homophilic adhesion. Key residues forming the binding site within this domain have been identified by analysis of 26 single point mutations, representing the most systematic analysis of a fully homophilic interaction between immunoglobulin superfamily family members to date. This revealed five mutations that affect homophilic binding. Uniquely, the residues involved are exposed on both faces of the immunoglobulin fold, leading us to propose a novel mechanism for CD31 homophilic adhesion.